UJI AKTIVITAS ANTIBAKTERI FUNGI ENDOFIT PADA DAUN SENGGANI (Melastoma malabathricum L.) ASAL LAMPARA MONCONGLOE TERHADAP BAKTERI PENYEBAB INFEKSI SALURAN PENCERNAAN - Hamdani, Nina; Kosman, Rachmat; Rusli, Rusli (PHARMACY UMI JOURNAL SYSTEM, 2023)
Senggani leaf (Melastoma malabathricum L.) is a plant that has antibacterial activity. The purpose of this study was to determine the isolate of the endophytic fungus senggani leaves (Melastoma malabathricum L.) which has antibacterial activity against digestive tract bacteria using the TLC-Bioautography method. The results of this study showed two isolates of senggani leaf endophytic fungi (Melastoma malabathricum L.). IFDS 6 obtained spots with Rf value = 0.58 for Eschericia coli bacteria, Rf value 0.67 for Vibrio cholerae, Salmonella typhi and Shigella dysentriae bacteria. Meanwhile, IFDS 8 obtained spots with an Rf value 0.78 on the bacteria Eschericia coli, Vibrio cholerae, Salmonella typhi, and Shigella dysentriae